Adsorption of lactoferrin and bovine serum albumin nanoparticles on pellicular two-layer agarose-nickel at reactive blue 4 in affinity chromatography. Issue 2 (April 2021) - Mofidian, Roozbeh; Xiong, Qingang; Ranjbar, Ali Mohammad; Sabbaghi, Mohammad Ali; Farhadi, Amin; Alizadeh, Seyed Mehdi
Abstract: In this study, adsorption of lactoferrin (Lf) and bovine serum albumin (BSA) nanoparticles on pellicular two-layer agarose-nickel immobilized by reactive blue 4 dye-ligand (2L-AN@RB4) was investigated. 2L-AN@RB4 was prepared using the three-phase emulsion method. The dynamic light scattering was first employed to quantify size distribution of Lf and BSA nanoparticles. Then, scanning electron microscopy (SEM) and atomic force microscope (AFM), respectively, were used to characterize structures of the two types of nanoparticles and adsorbent beads. SEM and AFM images demonstrate that shapes of the nanoparticles are globular and relatively uniform, where no adhesions were observed. Finally, adsorption behaviors of both Lf and BSA nanoparticles on 2L-AN@RB4 in affinity chromatography were investigated, with focus on the adsorption kinetics. Influences of contact time, pH, and initial concentration were analyzed to investigate the adsorbent behaviors in the expanded bed column. The influence of contact time on adsorption of Lf versus BSA nanoparticles indicates that 4 h is enough to adsorb protein models equal to 45%. Results indicate that Lf nanoparticles have a higher rate of around 83% than that of BSA nanoparticles. The increases in pH have negative effect on adsorption while opposite trend was found for initial concentration. Adsorption isotherm results reveal that the Langmuir and Freundlich isotherm models fit both adsorption kinetics of Lf and BSA very well. Graphical Abstract: ga1 Highlights: A novel two-layer AN@RB4 absorbent by three-phase emulsion method was fabricated. Absorptions of Lf and BSA nanoparticles by 2L-AN@RB4 were studied and compared. A pseudo-second-order model was proposed to fit the dynamic behavior of adsorbent. Effects of pH, contact time, and initial concentration on adsorption were studied. The Langmuir isotherm model was found to best describe the adsorption kinetics.